Artificial Neural Network Optimized Load Forecasting of Smartgrid using MATLAB - Ganthia, Bibhu Prasad; Mohanty, Monalisa; Mohapatra, Sushree Shataroopa; Pradhan, Rosalin; Satapathy, Subhasmita; Patra, Shilpa; Pahadasingh, Sunita Pahadasingh (Control Systems and Optimization Letters, 2023)
The motivation behind the research is the requirement of error-free load prediction for the power industries in India to assist the planners in making important decisions on unit commitments, energy trading, system security reliability, and optimal reserve capacity. The objective is to produce a desktop version of a personal computer-based complete expert system that can be used to forecast the future load of a smart grid. Using MATLAB, we can provide adequate user interfaces in graphical user interfaces. This paper devotes a study of load forecasting in smart grids, a detailed study of the architecture and configuration of Artificial Neural Network (ANN), Mathematical modeling and implementation of ANN using MATLAB, and a detailed study of load forecasting using the backpropagation algorithm.